Typology of cattle farms in a peasant community from southwest of Holguín, Cuba - Peña-Rueda, Y. F.; Benítez, D.; Ray, J.; Fernández-Romay, Yulien (Cuban Journal of Agricultural Science, 2018)
Facilitating processes of innovation and technology transfer in order to increase meat production led to create a typology of cattle farms in a peasant community from Southwest of Holguín. Data was taken from 21 farms, with variables: annual milk production, herd size, productivity, body condition, natural grass area and amount of paddocks. These variables were processed by principal components analysis in order to use factorial punctuations in a hierarchical cluster and k-means analyses. Four groupings were obtained, which describe typified farms as small (38.1 %), milk medium-sized (9.5 %), medium without specialization (19.0 %) and large (33.4 %). These last, besides natural grass Surface, milk production and meat productivity as reproducer, are different due to their contribution to animal welfare and to the relationship of production regime with the agroecosystem. Cattle farming in this region has proper infrastructure for milk production, so its functioning does not take into consideration many of the aspects that facilitate the organization of productive and reproductive processes of herd and the effective preparation to guarantee efficiency and avoid environmental degradation. It is suggested that agricultural extension activity focus on this diversity and complexity for generating programs that allow reaching an environmental balance, and, at the same time, strengthen cattle rearing in these communities. Key words: Classification, cattle, south agroecosystem, rural development, cluster analysis